Screening of microbial culture filtrates, plant extracts and fungicides for control of mango anthracnose (2012)
Anthracnose (Colletotrichum gloeosporioides) induces losses of up to 40% in most mango growing regions in Colombia. A series of exploratory experiments were carried out to evaluate 14 potentially antagonistic microorganisms, six plant extracts and 10 fungicides for disease control based on their ability to inhibit spore germination, mycelium growth and development of symptoms on detached fruits. In vitro experiments showed that spore germination of C. gloeosporioides was strongly inhibited (P≤0.0001) by all microbial culture filtrates, all fungicides and two plant extracts, suggesting that some of these treatments may hold promise for disease control. Similarly, all microbial filtrates, most fungicides and two plant extracts caused a significant (P≤0.0001) inhibition in mycelium growth of the pathogen. Results from this study indicated small effects of fungicides or plant extracts on anthracnose development on inoculated fruits, while microbial filtrates induced a significant reduction (P≤0.05) in lesion size. These results are very promising since current control practices rely on fungicides or costly physical treatments.